Internal structure of giant hail in a catastrophic event in Catalonia (NE Iberian Peninsula) - Farnell Barqué, Carme; Rigo, Tomeu; Martin-Vide, Javier; Úbeda, Xavier (Frontiers in Environmental Science, 2024)
On August 30, 2022, a giant hail-bearing supercell hit Catalonia (NE Iberian Peninsula), producing stones 12 cm in diameter. This is the most severe episode ever recorded in the country. Seventy people were injured, resulting in one fatality; several buildings were severely damaged, which resulted in substantial financial losses (more than e6M). In the present study, we analyze the stones collected during fieldwork to gather information on their growth processes. This analysis was conducted considering two lines of investigation. In this paper we focus on the innovative and never-before-used technique of the Computed Tomography Scan, which was utilized to analyze hailstones and their interiors, the outcomes were groundbreaking. It makes it possible to obtain a complete 3D view of the interior of the stone, without producing any alteration in the structure. Through this technology, the different layer densities have been quantified. This is the main novelty of the study and opens a promising door to more analyses in this field. The analysis has revealed some interesting results that help to verify previous theories. For instance, the nuclei can be placed far from the stone center, even if the hailstone is externally spherical.Besides, a thicker hailstone layer in one direction indicates the falling direction. Finally, the different layer densities show growth process variations.